Measurement of Local Gravity via a Cold Atom Interferometer - Zhou, Lin (林周); Xiong, Zong-Yuan (宗元 熊); Yang, Wei (威杨); Tang, Biao (彪汤); Peng, Wen-Cui (文翠 彭); Wang, Yi-Bo (一波 王); Xu, Peng (鹏许); Wang, Jin (谨王); Zhan, Ming-Sheng (明生 詹) (Chinese physics letters, 2011)
We demonstrate a precision measurement of local gravity acceleration 9 in Wuhan by a compact cold atom interferometer. The atom interferometer is in vertical Mach-Zehnder configuration realized using a 7r /2 - π - π /2 Raman pulse sequence. Cold atoms were prepared in a magneto-optical trap, launched upward to form an atom fountain, and then coherently manipulated to interfere by stimulated Raman transition. Population signal vs Raman laser phase was recorded as interference fringes, and the local gravity was deduced from the interference signal. We have obtained a resolution of 7 × 10-9g after an integration time of 236s under the best vibrational environment conditions. The absolute g value was derived from the chirp rate with a difference of 1.5 × 10--07 g compared to the gravity reference value. The tidal phenomenon was observed by continuously monitoring the local gravity over 123 h.